Struggle Of Hazel's Against Cancer In Novel The Fault In Our Stars (2014) By John Green:An Individual Psychological Approach - Oktaviani, Ruri Ratna; , Titis Setyabudi, S.S. M. Hum (2016)
The main problem of this study is a struggle. A person who has cancer can live normal. This study is to analyze the novel The Fault In Our Stars based on the theory of individual psychology. The author uses a qualitative method. The author uses two data sources: primary and secondary. The primary data source is The Fault In Our Stars by John Green novel. Secondary data is data taken from some books supporting the theory of individual psychology, and some articles from the internet related to the novel. The writer took some conclusions. This study shows that a problem faced by the main character was her recover. Based on this analysis, the author gets some conclusions. This study shows that the problemfaced by the main character was his struggle against cancer. This is evidenced by his desire to do healing and therapy. It is evidenced by the hard work of the main characters in realizing his desire to get recovery